A Study to Assess the Effectiveness of Structured Teaching Programme on Behavioural Disorder and Its Management Among Primary School Teachers in Thruvirkadu, Chennai. - E. Kannagi, E. Kannagi; S. Rajalakshmi, S. Rajalakshmi (Journal of Neonatal Surgery, 2025)
Background: Behavioral disorders in school children represent a significant concern for educators, parents, and mental health professionals, as these disorders can profoundly affect a child's learning, social interactions, and overall development. The study aimed to assess the effectiveness of structured teaching programme on behavioural disorder and its management among primary school teachers in Thruvirkadu, Chennai. Methodology: This study utilized an experimental one-group pretest-posttest design to evaluate the effectiveness of a structured teaching program on the knowledge of primary school teachers regarding behavioral disorders and their management. A quasi-experimental approach was adopted to measure the change in knowledge levels before and after the intervention. The study was conducted in a primary school in Thiruverkadu, Chennai, where the structured teaching program was implemented over a specified period. The setting allowed for direct interaction with teachers and easy administration of the program. The study involved a total of 30 primary school teachers who were selected using a convenience sampling technique. Results: The study found that during the pretest, all 30 (100%) teachers demonstrated inadequate knowledge regarding behavioral disorders and their management. After the structured teaching program, all 30 teachers (100%) showed adequate knowledge in the posttest, indicating a significant improvement. The mean pretest knowledge score was 5.13 (SD = 1.33), while the mean posttest knowledge score increased to 14.83 (SD = 1.05), with a difference of 9.70. The calculated t-value was 31.35, which was much higher than the expected t-value of 2.064, and the p-value was less than 0.05, confirming that the difference was statistically significant. Conclusion: The study highlighted that the intervention had a positive impact on children's health metrics, with significant reductions in BMI, waist circumference, and body fat percentage